Stability and degradation patterns of chemically modified analogs of apelin‐13 in plasma and cerebrospinal fluid. Issue 4 (July 2014) - Murza, Alexandre; Belleville, Karine; Longpré, Jean‐Michel; Sarret, Philippe; Marsault, Éric
ABSTRACT Apelin is the endogenous ligand of APJ, which belongs to the superfamily of G protein‐coupled receptors. In recent years, the apelin/APJ system has been detected in many tissues and emerges as a promising target for the treatment of various pathophysiological conditions. Pyr1‐apelin‐13 is the major isoform of apelin in human plasma; however its stability and proteolytic degradation pattern remain poorly understood. The aim of the present study was first to identify the cleavage sites of Pyr1‐apelin‐13 in mouse, rat and human plasma and rat cerebrospinal fluid, then to determine its stability to proteolytic degradation following intravenous administration in rats. Secondly, key residues were substituted by natural and unnatural amino acids in order to examine the impact on in vitro stability and degradation pattern. The kinetics of degradation revealed that the Leu5‐Ser6 peptide bond of Pyr1‐apelin‐13 is the first cleavage observed in plasma, independently of the species. Replacement of Phe13 by unnatural amino acids showed a 10‐fold increase in plasma stability although the hydrolysis of Pro12‐Phe13 bond, previously described as a site of cleavage by ACE‐2, was not observed. In vivo, this Pro12‐Phe13 bond was cleaved yet appears as a minor product compared to hydrolysis of the Pro10‐Met11 bond. This study pinpoints the most critical amino acids targeted by proteases and will be instrumental for the design of Pyr1‐apelin‐13 analogs possessing increased stability. © 2014 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 297–303, 2014.